2014
DOI: 10.1111/jcpp.12337
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in ADHD symptom severity

Abstract: Background Males show higher rates of attention deficit hyperactivity disorder (ADHD) than do females. Potential explanations include genuine etiological differences or artifact. Methods 2,332 twin and sibling youth participated in behavioral and cognitive testing. Partially competing models of symptom severity distribution differences, the mean difference and variance difference models, were tested within a randomly selected subsample. The Delta method was used to test for mediation of sex differences in AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
161
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 271 publications
(184 citation statements)
references
References 37 publications
18
161
1
4
Order By: Relevance
“…Findings that there are true gender differences in ADHD symptoms between males and females in population-based samples (Arnett et al, 2015) do not rule out the possibility that some of the observed variation in ADHD symptoms between genders can be accounted for by biases in referral to clinical services. Males may be over-referred and over-diagnosed in childhood and/or females may be underidentified or referred in childhood.…”
Section: Referral or Identification Biasesmentioning
confidence: 72%
See 2 more Smart Citations
“…Findings that there are true gender differences in ADHD symptoms between males and females in population-based samples (Arnett et al, 2015) do not rule out the possibility that some of the observed variation in ADHD symptoms between genders can be accounted for by biases in referral to clinical services. Males may be over-referred and over-diagnosed in childhood and/or females may be underidentified or referred in childhood.…”
Section: Referral or Identification Biasesmentioning
confidence: 72%
“…Supporting the explanation of true differences, Arnett et al (2015) recently confirmed that boys have more childhood ADHD symptoms than girls, even after accounting for issues of selection bias, measurement invariance, and the possibility that a particularly types of symptoms (e.g., symptoms of Sluggish Cognitive Tempo) which better characterize ADHD in girls are missing from the diagnostic criteria. In a meta-regression, Simon, Czobor, Bálint, Mészáros, and Bitter (2009)found that when samples were predominantly male, ADHD prevalence was more likely to decrease as age increased.…”
Section: True Differencesmentioning
confidence: 87%
See 1 more Smart Citation
“…This may explain the significance of gender as a predictor of symptom intensity in the present study. Additionally Arnett et al 36 have demonstrated that gender and symptom severity are mediated by genetic factors, suggesting the need for a more comprehensive explanatory framework for the relationship between ADHD symptom severity and gender, since there is no consensus in the literature regarding the association between these variables, many studies continue to demonstrate an absence of gender differences in the presentation of this disorder. 9,31 The impact of age on the severity of inattention symptoms may be related to the developmental trajectory of the executive functions in childhood, which accompanies the maturation of cognitive attentional processes and their structural/functional neural correlates.…”
Section: Discussionmentioning
confidence: 99%
“…Arnett et al 36 have identified significant differences in symptom severity between boys and girls with ADHD, which appear to be moderated by cognitive variables such as processing speed, inhibition and working memory. This may explain the significance of gender as a predictor of symptom intensity in the present study.…”
Section: Discussionmentioning
confidence: 99%